Malignant Subdural Hematoma Associated with High-Grade Meningioma - Teramoto, Shinichiro; Tsunoda, Akira; Kawamura, Kaito; Sugiyama, Natsuki; Saito, Rikizo; Maruki, Chikashi (The Surgery Journal, 2018)
A 70-year-old man, who had previously undergone surgical resection of left parasagittal meningioma involving the middle third of the superior sagittal sinus (SSS) two times, presented with recurrence of the tumor. We performed removal of the tumor combined with SSS resection as Simpson grade II. After tumor removal, since a left dominant bilateral chronic subdural hematoma (CSDH) appeared, it was treated by burr hole surgery. However, because the CSDH rapidly and repeatedly recurred and eventually changed to acute subdural hematoma, elimination of the hematoma with craniotomy was accomplished. The patient unfortunately died of worsening of general condition despite aggressive treatment. Histopathology of brain autopsy showed invasion of anaplastic meningioma cells spreading to the whole outer membrane of the subdural hematoma. Subdural hematoma is less commonly associated with meningioma. Our case indicates the possibility that subdural hematoma associated with meningioma is formed by a different mechanism from those reported previously.
Keywords: high-grade meningioma; recurrent chronic subdural hematoma; outer membrane of subdural hematoma